Multi-component non-fullerene acceptors with tunable bandgap structures for efficient organic solar cells. Issue 46 (14th November 2018) - Gao, Bowei; Yao, Huifeng; Hou, Junxian; Yu, Runnan; Hong, Ling; Xu, Ye; Hou, Jianhui
Abstract : Six-component OSCs are fabricated by selecting one donor and five non-fullerene acceptors, exhibiting easily tuned current and voltage. Abstract : A ternary organic solar cell, consisting of two compatible non-fullerene acceptors and one wide band-gap donor, with a high efficiency of over 14% is reported, and the working mechanism of the bandgap structure modulation is studied. Based on that, we fabricate six-component OSCs by selecting one donor and five non-fullerene acceptors, exhibiting easily tuned current and voltage.